NOVA: Nottingham Off-road Vehicle Architecture - Strachan, Jamie Robert (2009)
This thesis describes a program of research aimed at the creation of an unmanned ground vehicle. In this research the Nottingham Off-road Vehicle Architecture (NOVA) was developed along with the ARP (Autonomous Route Proving vehicle. NOVA is a control architecture for a vehicle with the role of autonomous route proving in natural terrain. The ARP vehicle was constructed to demonstrate this architecture.